The mutation of ent-kaurene synthase, a key enzyme involved in gibberellin biosynthesis, confers a non-heading phenotype to Chinese cabbage (Brassica rapa L. ssp. pekinensis). (1st November 2020) - Gao, Yue; Huang, Shengnan; Qu, Gaoyang; Fu, Wei; Zhang, Meidi; Liu, Zhiyong; Feng, Hui
Abstract: The presence of a leafy head is a vital agronomic trait that facilitates the evaluation of the yield and quality of Chinese cabbage. A non-heading mutant ( nhm1 ) was identified in an ethyl methanesulfonate mutagenesis population of the heading Chinese cabbage double haploid line FT. Segregation analysis revealed that a single recessive gene, Brnhm1, controlled the mutant phenotype. Using MutMap, Kompetitive allele-specific PCR, and cloning analyses, we demonstrated that BraA07g042410.3C, which encodes an ent -kaurene synthase involved in the gibberellin biosynthesis pathway, is the nhm1 mutant candidate gene. A single-nucleotide mutation (C to T) in the fourth exon of BraA07g042410.3C caused an amino acid substitution from histidine to tyrosine. Compared to that of the wild-type FT, BraA07g042410.3C in the leaves of the nhm1 mutant had lower levels of expression. In addition, gibberellin contents were lower in the mutant than in the wild type, and the mutant plant phenotype could be restored to that of the wild type after exogenous GA3 treatment. These results indicate that BraA07g042410.3C caused the non-heading mutation. This is the first study to demonstrate a relationship between gibberellin content in the leaves and leafy head formation in Chinese cabbage. These findings facilitate the understanding of the mechanisms underlying leafy head development in Chinese cabbage.